2020
DOI: 10.1016/j.tcb.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

EMT, MET, Plasticity, and Tumor Metastasis

Abstract: Cancer cell identity and plasticity are required in transition states, such as epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET), in primary tumor initiation, progression and metastasis. The functional roles of EMT, MET and partial state (referred to as p-EMT) may vary based upon the type of tumor, state of dissemination and degree of metastatic colonization. Herein, we review EMT, MET, pEMT and plasticity in the context of tumor metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
491
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 671 publications
(501 citation statements)
references
References 79 publications
(96 reference statements)
10
491
0
Order By: Relevance
“…Metastasis is one of the most important characteristics of malignant tumors and often results in treatment failure and poor prognosis. 34 Mounting evidence has confirmed that ezrin and MMP2 are critical molecules involved in migration and invasion of tumors including cervical cancer. 35 , 36 In our study, quercetin enhanced the inhibitory effect of cisplatin on the migration and invasion of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is one of the most important characteristics of malignant tumors and often results in treatment failure and poor prognosis. 34 Mounting evidence has confirmed that ezrin and MMP2 are critical molecules involved in migration and invasion of tumors including cervical cancer. 35 , 36 In our study, quercetin enhanced the inhibitory effect of cisplatin on the migration and invasion of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial–mesenchymal transition (EMT) is a phenomenon of epithelial cells transforming into mesenchymal cells, which is a process of cell dedifferentiation or redifferentiation [ 6 ]. Through the EMT process, the migration and motility of cancer cells are enhanced, contributing to the invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, SRGAP2 knockdown could not alter the expression of epithelial marker (E-cadherin) and mesenchymal markers (Ncadherin and vimentin). Although it is reported that EMT plays a critical role in rst step of the metastatic process [30], tumor metastasis also often occurs without stimulating EMT program [31]. A recent study shows that AKT-induced lncRNA VAL could promote metastasis of lung adenocarcinoma in the absence of activating EMT [32].…”
Section: Discussionmentioning
confidence: 99%